Signs and discourses in John 5 and 6: historical, literary, and theological readings from the Colloquium Ioanneum 2019 in Eisenach - Frey, Jörg; Koester, Craig R. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
Cover -- Title -- Foreword -- Table of Contents -- George Parsenios - The "Man at the Pool" and the "Man Born Blind": Comparison in the Lives of Plutarch and the Gospel of John -- Christos Karakolis - The Lame Man (John 5:1-18) as a Model for the Johannine Jews: A Narrative and Reader-Response Analysis -- Adele Reinhartz - Doing God's Work: John 5:17-18 from a Jewish Perspective -- Jörg Frey - Who Should "Not Wonder"? On the Audience and Logical Structure of the Discourse-Section John 5:19-30 -- R. Alan Culpepper - Jesus the Judge (John 5:21-30): The Theme of Judgment in John's Gospel -- Ruben Zimmermann/Zacharias Shoukry - Creatio Continua in the Fourth Gospel: Motifs of Creation in John 5-6 -- Jean Zumstein - The Construction of Space in John 5-6 -- Michael Labahn - Jesus: Gottes Gabe in der Not. Theologische und christologische Charakterisierung Jesu und seiner Jünger im Vergleich zwischen Mk 6:30-52 und Joh 6:1-21 -- Craig R. Koester - Signs and Christology in John 6:1-21 in Light of Jewish and Greco-Roman Frames of Reference: Prophet, King, and Revealer of God -- Catrin H. Williams - Intertextual Perspectives on John's Sea-Crossing Account (John 6:16-21) -- William Loader - Soteriology and Spirituality in John 6: A Reflection on Key Issues in Johannine Theology -- Michael Theobald - „Diese Rede ist hart" (Joh 6:60): Wider die Versuchung, Joh 6:51e-58 bildlich zu verstehen -- Udo Schnelle - Johannes 6:60-71 und die Genese der johanneischen Theologie -- Marianne Meye Thompson - "Many of His Disciples Turned Back": The Offense of Jesus's Death in the Gospel of John (John 6:60-71) -- D. Francois Tolmie - Elected and a Devil? The Characterization of Judas Iscariot in the Fourth Gospel -- Bibliography -- List of Contributors -- Index of Ancient Sources -- Index of Authors -- Index of Subjects.